Variance-Corrected Proportional Hazard Models for the Analysis of Multiple Failures in Personal Computers - Sunethra, A. A.; Sooriyarachchi, M.R. (Wiley InterScience, 2011)
Proportional hazard (PH) modeling is widely used in several areas of study to estimate the effect of covariates on event timing. In this paper, this model is explored for the analysis of multiple occurrences of hardware failures in personal computers. Multiple failure events consist of correlated data, and thus the assumption of independence among failure times is violated. This study critically describes a class of models known as variance-corrected PH models for modeling multiple failure time data, without assuming independence among failure times. The objective of this study is to determine the effect of the computer brand on event timings of hardware failures and to test whether this effect varies over multiple failure occurrences. This study revealed that the computer brand affects hardware failure event timing and that further, this effect of the brand does not change over the multiple failure occurrences.
Keywords: multiple failures; variance-corrected proportional hazard models; information matrix test; modified variance sandwich estimator; risk interval; risk set